Tingginya Mutu Pelayanan Keperawatan Berpengaruh terhadap Kepuasan Pasien di BLUD RS Benyamin Guluh Kolaka - Evodius Nasus; Grace Tedy Tulak (Jurnal Surya Medika (JSM), 2020)
Hospitals as health service providers are expected to always prioritize patient satisfaction through improving the quality of services performed. One indicator to assess the quality of health services is to measure the level of satisfaction of patients who are recipients of health services. This research aims to analyze the effect of the quality of nursing services with patient satisfaction at BLUD Benyamin Guluh Kolaka Hospital. The research method used was an analytic survey with a cross-sectional approach. The population and sample were 75 patients in the internal and surgical rooms which were obtained by the accidental sampling method. The results result showed that significantly the high quality of nursing services can affect patient satisfaction (p=0.000 < p=0.05). The conclusion of this study is that the higher the quality of nursing services, the more positive impact on satisfaction felt by patients otherwise.